Pemetaan SMK Di Jawa Barat, Bangka Belitung dan Kalimantan Tengah - Mulyadi, Yadi; Mukhidin, Mukhidin; Setiawan, Agus; Hamdani, Aam; Purnawan, Purnawan (INVOTEC, 2010)
Since 2005 the Directorate of Vocational High School Development (Direktorat PSMK)  has launched a national program  of vocational  high school  (SMK) development on a large scale with the scenario of increasing the quantity vocational high school students and reducing the number of senior high school students (SMA) or known by the scheme of 70:30. Its fundamental consideration is to reduce the unemployment rate of SMA graduates can who not continue to studies to their  further higher level of education. While the development of vocational education is expected to expand the employment absorption in the greater world of industry. The implications to the above national program  significance  of the increasing numbers of new SMK spreading from both in urban and rural .  Some of both public and private vocational schools has emerged  quickly, even in some areas there are primary school, junior or vocational school used to make the CMS. This condition is certainly  worrying, on the one side it is  line with the national program but on the other side the increase in quantity does not  linearly correlate with the quality. More over  the relevence of the SMK competence  program has not been thoroughly examined an in depth study that  can give an impact on the employment  absorption in the world of indutry. Aperiodically comprehensive mapping of the all existing vocational the schools need tobe done ranging especially  from the availability of the  teachers the program expertise as well as the and the infrastructure as well as development of the  students, including the increasing the number of teachers, the interest of the community as well as  programs being carried out in SMK. The method used in conducting the research is a descriptive method, this method describes the condition of the existing vocational schools in each subject study area. Data is  collected through using the census method and documentation methods. This research has produced data for all three subject study areas in  West Java, Bangka Belitung  and Central Kalimantan and has sequentially  resulted as follows: (1) Number of SMK: 1043, 43, 67, (2) Number learning group: 9454, 418, 446, (3) Number of learning resource centre: 134 988, 5782, 5764, (4) Number of Students: 327,757, 14,482, 14,010, (5) Number of graduates: 81 916, 2517, 2586.